Variation in menopausal vasomotor symptoms outcomes in clinical trials: a systematic review. (13th November 2019) - Iliodromiti, S; Wang, W; Lumsden, MA; Hunter, MS; Bell, R; Mishra, G; Hickey, M
Abstract : Background: There is substantial variation in how menopausal vasomotor symptoms are reported and measured among intervention studies. This has prevented meaningful comparisons between treatments and limited data synthesis. Objectives: To review systematically the outcome reporting and measures used to assess menopausal vasomotor symptoms from randomised controlled trials of treatments. Search strategy: We searched MEDLINE, Embase, and Cochrane Central Register of Controlled Trials from inception to May 2018. Selection criteria: Randomised controlled trials with a primary outcome of menopausal vasomotor symptoms in women and a sample size of at least 20 women per study arm. Data collection and analysis: Data about study characteristics, primary vasomotor‐related outcomes and methods of measuring them. Main results: The search identified 5591 studies, 214 of which were included. Forty‐nine different primary reported outcomes were identified for vasomotor symptoms and 16 different tools had been used to measure these outcomes. The most commonly reported outcomes were frequency (97/214), severity (116/214), and intensity (28/114) of vasomotor symptoms or a composite of these outcomes (68/214). There was little consistency in how the frequency and severity/intensity of vasomotor symptoms were defined. Conclusions: There is substantial variation in how menopausal vasomotor symptoms have been reported and measured in treatment trials. Future studies should include standardised outcome measures which reflect the priorities of patients, clinicians, and researchers. This is most effectively achieved through the development of a Core Outcome Set. This systematic review is the first step towards development of a Core Outcome Set for menopausal vasomotor symptoms. Tweetable summary: Menopausal hot flushes and night sweats have been reported in 49 different ways in clinical research. A core outcome set is urgently required. Tweetable summary: Menopausal hot flushes and night sweats have been reported in 49 different ways in clinical research. A core outcome set is urgently required.